CURRICULUM INNOVATION IN SCIENCE TEACHING FOR TECHNOLOGICAL COMPETITIVENESS IN AN ERA OF INSECURITY AND ECONOMIC MELTDOWN (UNIZIK Journal of STM Education, 2025)
Science education plays a pivotal role in equipping learners with mindset, knowledge and skills needed to contribute and thrive in innovation-based economies and promoting technological competitiveness through science teaching and learning is important in a more coordinated and technological driven-world. Curriculum  innovation in science teaching and learning becomes essential to ensure that students are literate in both scientific principles and its applications creatively and critically in technological and engineering contexts by employing project based learning, collaborative problem solving and the integration of digital tools which will help learners steer through modern science and technological competitiveness at the national and global levels depends heavily on how well students are prepared to tackle scientific and technological challenges. This paper therefore, explores the curriculum innovation in science teaching for technological competitiveness. The curriculum innovation employed should demonstrate improved students’ engagement, conceptual understanding and readiness for future technological advancement and the curriculum itself should serve as a tool for educational institution to inculcate the knowledge of science and the skills to apply technological advancement in driving innovation and competitiveness in a global economy and also the curriculum should be dynamic, interdisciplinary and forward looking by fostering creativity, scientific curiosity and technological proficiency, which will help prepare a generation that can adapt to and lead to technological leadership tomorrow.
Keywords: Curriculum Innovation, Science Teaching and Learning, Science Teaching for Technological Competitiveness, Technological Competitiveness